2001
DOI: 10.1007/s004170000237
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative capacity of various artificial tear preparations

Abstract: The anti-oxidative capacity of artificial tear preparations varies widely. While some are strong anti-oxidants, others are less active or even act as oxidants. If the carefully elicited history of patients with dry eyes suggests that noxious environmental factors may be causally involved, artificial tears which are not just lubricants or contain wetting agents, but act as anti-oxidants, should be chosen for treatment from the many commercially available preparations. Such an etiology-oriented concept would pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…These results indicate that eye drops containing hyaluronic acid 0.15 % and vitamin B12 improve oxidative stress as well as symptoms of dry eye. Our findings The P-value was calculated by t test are supported by recent studies that have also shown that hyaluronic acid and vitamin B12 have antioxidant activity in ophthalmology and other diseases involving ROS [31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 86%
“…These results indicate that eye drops containing hyaluronic acid 0.15 % and vitamin B12 improve oxidative stress as well as symptoms of dry eye. Our findings The P-value was calculated by t test are supported by recent studies that have also shown that hyaluronic acid and vitamin B12 have antioxidant activity in ophthalmology and other diseases involving ROS [31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 86%
“…The significant improvement of the antioxidative protective capacity of the tear fluid by iodide iontophoresis in Bad Hall/ Austria is certainly an essential expansion of the treatment of dry eye syndrome, especially in cases with oxidative stress to the ocular surface [5,9,21,31,32,54,57,61,64] Further investigations are needed to elucidate iodine effects on other factors of dry eye disorders, for instance inflammation, which is another important finding in dry eye syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of protection by iodide is likely to include an antioxidative action as discussed by several authors [31,45,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In preparations containing iodide, antioxidative and radical scavenger effects have been observed [31,45,47,48]. Also treatment of the ocular surface with brine containing iodide contributes to an increase of the antioxidant status in tear fluid [32].…”
Section: Introductionmentioning
confidence: 99%